Modern nursing care of the patient affected Parkinson - Kosek-Hoehne, Karolina; Guty, Edyta; Śliwa, Anna; Panocha, Błażej (Journal of Education, Health and Sport, 2017)
Parkinson’s disease or shaking palsy is one of the most frequent degenerative diseases of nervous system which concerns extrapyramidal system. The thesis shows nursing work during long term care which involves health problems and social, cultural and educational conditions of patients and their families. If we talk about medical care and Parkinson’s disease patients the biggest problem is professional care in patients’ habitat, mainly in their homes or special care centres. Nurses’ qualified and care skills and their professional help make possible to supplement therapy, rehabilitation of older patients, chronic patients, physical and intelectual disabled people and patients with mental disorders. There are also conditions to create self-care and self-nursery which are improved all the time. The main source of nursery problems with this disease are motor and vegetative symptoms, motor complications and mental reaction for progressing disease. The aim of nursery care is to help the patient to stay independent as long as possible, to satisfy needs, to make mental and physical adaptation easier, to understand and accept the disease and to support patients so the social isolation would not increase.